PENINGKATAN PENGETAHUAN TENTANG SCHISTOSOMIASIS PADA GURU DAN MURID SEKOLAH DASAR DI KECAMATAN LORE BARAT KABUPATEN POSO - Meiske Elisabeth Koraag; Rosmini Rosmini; Anis Nurwidayati; Sitti Chadijah; Mujiyanto Mujiyanto; Ni Nyoman Veridiana; Intan Tolistiawaty (Balai Besar Penelitian dan Pengembangan Vektor dan Reservoir Penyakit (B2P2VRP) Salatiga, 2019)
The provision of knowledge on schistosomiasis to the students and teachers of elementary schools increase their knowledge and affected the coverage of stool collection. Teachers and students are also expected to be able to provide information about the schistosomiasis which they have obtained to their families and communities around them. This research aimed to assess the success of the training of teachers and students in the control of schistosomiasis. This research was intervention research that used quasi-experiment design. The intervention was conducted by providing socialization about schistosmiasis to students and teachers in classrooms, followed by the practice in the field. The intervention and control group comprised 63 students and teachers. Evaluation of the teachers and students knowledge about schistosomiasis was conducted by questionnaire. The results of this research showed that in the intervention group, there was a significant increase in the knowledge from pre-test 9,25 to post-test 16,86 (p = 0.000). The provision of intervention in the form of knowledge to students and teacher has significantly increased the knowledge about epidemiology, treatment and surveillance schistosomiasis.